Dinamika Sengketa Tanah Warisan dalam Masyarakat Pedesaan: Studi Kasus Relasi Kekeluargaan dan Kepemilikan Tanah di Kabupaten Sampang - Maulana Arfidata Reyhan; Rafli Akmal Athallah (Lembaga Pengembangan Kinerja Dosen, 2025)
Land disputes in rural Indonesia reveal the tension between formal law and localized social practices. This study examines a legal case involving a foster grandchild and long-standing landholders, based on Supreme Court Decision No. 1250 K/Pdt/2012. The analysis focuses on legal certainty, the legal standing of foster children, the absence of immaterial damages claims, and the potential for legal innovation. The study suggests that stronger recognition of social-administrative ties in non-biological family relations may serve as a novel approach for reforming property inheritance law.